Properties Of Waste Polyethylene Terphthalate (Pet) Tile Containing Fly Ash And Palm Oil Fuel Ash Aggregates Towards Sustainable Construction Material - Oluwakemi, Omosebi Taiwo (2023)
The fast expansion of the global construction sector has a significant impact on the cost of building materials, and also the natural resources required for the materials' production and the environment. Plastic waste management on the other hand is a global issue that poses a threat to our environment’s health because of its high manufacturing rate and inability to biodegrade. The opportunity to turn waste plastics into new construction materials would be a major gain. This study examines the application of polyethylene terephthalate (PET) waste bottles, river sand, fly ash, and palm oil fuel ash (POFA) to produce tiles. Physical and mechanical characteristics such as density, porosity, water absorption, compressive strength, flexural strength, flammability, wear-abrasion resistance, thermal stability, and chemical tolerance of the manufactured Polymer tiles and also the PET paste and sand microstructure interaction have been investigated. PET waste was utilized in varying quantities (30 %, 50%, 70%, 90%, and 100 %) of sand, fly ash, and POFA by weight. The evaluation of the mechanical and physical characteristics of the materials demonstrated that the tiles with a 30% PET content performed better in terms of material density, strength properties, flame resistance, and thermal stability than others. The maximum compressive strength values of 19.71, 6.88, and 8.37 MPa were found in the polymer tiles made of sand, fly ash, and POFA respectively, in this study, the highest compressive strength was greater than the control sample. Also, polymer tiles have a very miniature percentage of water absorption in comparison to ceramic and cement tiles. The percentage of water absorption is between 0.1% - 1.91%.